Shaping Inclusive Workplaces for Persons with Disabilities: A Management and HRM Practitioner Perspective (Business and Management; Business and Management (R0), 2026)
Despite the increase in research about workplace inclusion, the current literature is dominated by a negative focus on the barriers managers face as they attempt to hire people from disadvantaged groups, including people with disabilities. This open access book offers a positive and practical guide to workplace inclusion that focuses on the opportunities and strategies for managers to succeed and to develop and capitalize on the strengths and resources of individuals. Unlike some works with a broader societal focus, this contributed volume puts the spotlight firmly on what happens inside workplaces and organizations. It shifts focus from a reactive view of organizations acting on external motivations and pressures towards a proactive view, based on internal motivation, opportunities, and untapped resources. Each chapter is written on a specific theme by a leading expert, digesting the theory and applying it to real-world cases. It will be of great interest to executive education and MBA students, as well as HR practitioners and policymakers.